2015
DOI: 10.1039/c4ce02262a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of porous rh-In2O3nanostructures with visible-light-driven photocatalytic degradation of tetracycline

Abstract: In this paper, well-defined 3D flower-like porous rhombohedral In2O3(rh-In2O3) nanostructures were successfully synthesizedviathe hydrothermal method combined with post-thermal treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 48 publications
0
21
0
4
Order By: Relevance
“…The unique rod-in-tube structure afforded excellent photocatalytic activity towards the degradation of TC; the structure enhanced light utilisation by light refraction and reflection. Additionally, the authors demonstrated the potential of rhombohedral In2O3 with well-defined, three-dimensional, flower-like porous nanostructures as a visible-light photocatalyst for the photocatalytic degradation of TC [49]. When compared with bulk In2O3, the three-dimensional, flower-like porous rhombohedral In2O3 displayed a higher photocatalytic performance, which was attributed to the nature of the crystal phase and high charge separation efficiency.…”
Section: Visible Light-driven Semiconductor Photocatalystsmentioning
confidence: 98%
“…The unique rod-in-tube structure afforded excellent photocatalytic activity towards the degradation of TC; the structure enhanced light utilisation by light refraction and reflection. Additionally, the authors demonstrated the potential of rhombohedral In2O3 with well-defined, three-dimensional, flower-like porous nanostructures as a visible-light photocatalyst for the photocatalytic degradation of TC [49]. When compared with bulk In2O3, the three-dimensional, flower-like porous rhombohedral In2O3 displayed a higher photocatalytic performance, which was attributed to the nature of the crystal phase and high charge separation efficiency.…”
Section: Visible Light-driven Semiconductor Photocatalystsmentioning
confidence: 98%
“…The corundum structure of In2O3 has 7 Raman-active modes whose frequencies at ambient pressure have been already reported in bulk and nanocrystals. 22,30,37,39,40 Figure 3 shows selected 39 and 3D rh-In2O3 nanoflowers 40 were characterized by XRD and Raman spectroscopy at room conditions. In the former geometry, the Raman spectrum showed peaks at 164, 222, 273, 385, 504, and 595 cm -1 whereas in the latter, the Raman modes appeared at 163, 219, 384, 501 and 590 cm -1 .…”
Section: Raman Scatteringmentioning
confidence: 99%
“…rice-grain type have been grown in the last decade. 39,40 A priori, we expect that all nanoparticles with similar size behave in a similar way. 79 In any case, future HP experiments using rh-In2O3 nanocrystals with different morphologies will help to understand the HP behaviour of rh-In2O3 nanocrystals.…”
Section: Raman Scatteringmentioning
confidence: 99%
“…In recent years, indium oxide (In 2 O 3 ) which is a very important wideband‐gap (direct band gap around 3.6 eV), n‐type transparent semiconductor has been extensively studied due to its potential applications such as solar cells, liquid‐crystal display [9], photocatalyst [10, 11], and ultrasensitive gas sensor for detection of O 3 [12], CO 2 [13], NO 2 [14], HCHO [15], acetone [16], and Cl 2 [15]. To date, various morphologies of In 2 O 3 have been fabricated via different methods.…”
Section: Introductionmentioning
confidence: 99%